2018
DOI: 10.1093/eurheartj/ehy446
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic syndrome with non-thromboembolic adverse cardiac outcomes in patients with atrial fibrillation

Abstract: Metabolic syndrome is common in AF patients without overt CAD, and confers an independent, increased risk of MACE, including MI, coronary revascularization, and cardiac death. Given its prognostic implications, prevention and treatment of MetS may reduce the burden of non-thromboembolic complications in AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Possibly, this may indicate that AF patients with T2DM suffered a larger MI with a devastating effect on left ventricular systolic function and consequent HFrEF. Previous research may support this view by showing a stronger propensity for incident MI or CV death among AF patients with metabolic syndrome (which often precedes overt T2DM) compared to those without . This is also in line with the above‐noted lower relative T2DM‐related risk of adverse outcomes in patients with reduced baseline LVEF, in whom prior burden of vascular disease and interim ACS might have mitigated the absolute effect of T2DM, but at the same time, increased the likelihood of HFrEF.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Possibly, this may indicate that AF patients with T2DM suffered a larger MI with a devastating effect on left ventricular systolic function and consequent HFrEF. Previous research may support this view by showing a stronger propensity for incident MI or CV death among AF patients with metabolic syndrome (which often precedes overt T2DM) compared to those without . This is also in line with the above‐noted lower relative T2DM‐related risk of adverse outcomes in patients with reduced baseline LVEF, in whom prior burden of vascular disease and interim ACS might have mitigated the absolute effect of T2DM, but at the same time, increased the likelihood of HFrEF.…”
Section: Discussionsupporting
confidence: 76%
“…When patients with new-onset HF were divided by baseline T2DM status and an interim ACS (i.e. with or without ACS preceding new-onset HF), a divergence in distribution of HF phenotypes was observed among the subgroups (Figure 3) 51 This is also in line with the above-noted lower relative T2DM-related risk of adverse outcomes in patients with reduced baseline LVEF, in whom prior burden of vascular disease and interim ACS might have mitigated the absolute effect of T2DM, but at the same time, increased the likelihood of HFrEF. However, more precise interpretation of these findings is largely limited by a small number of events.…”
Section: The Association Between Type 2 Diabetes and New-onset Heart mentioning
confidence: 99%
“…15 In particular, patients with AF deserve careful assessment, given the high prevalence and increased risk of adverse outcomes in the presence of the metabolic syndrome. 16 In addition, the present study extends current knowledge and promotes further research into potentially modifiable risk factors for common cardiovascular disorders, including AF.…”
supporting
confidence: 66%
“…Previous studies on clinical observation have reported that MetS is associated with AF risk; this association is observed in western populations [18][19][20], and also in Asian countries [21][22][23]. MetS is common in AF patients without overt coronary heart diseases, and is independently correlated with increased risk of cardiac death [24]. In addition, MetS also has an impact on the outcome and recurrence risk of AF after a catheter ablation termination [25,26].…”
Section: Mets Is a Major Risk For Atrial Cardiomyopathy And Afmentioning
confidence: 90%